Ecological assessment of groundwater at the airport zone - Madzhd, Svitlana; Cherniak, Larysa; Mikhyeyev, Oleksandr (My University, 2022)
In complex natural, technogenic and anthropogenic conditions, when at the same time the quality of water directly in the underground part of the Hydrosphere or through other components of the environment is affected by various factors of pollution, the assessment of the quality of underground water takes on a specific character. Carrying out constant monitoring of the state of the groundwater, comparing and assessing the compliance of pollutant concentrations with established standards makes it possible to assess the actual state of groundwater in the airport area and adjacent territories for the content of pollutants. The main sources of groundwater pollution as a result of the operation of aviation equipment are rainwater and meltwater, emergency discharges of petrochemicals, fuel and lubricant storage farms. The purpose of the work: to carry out an ecological assessment of the quality of groundwater at the area of the International Airport Kyiv (Zhulyany) according to the main hydro-ecological indicators. The water quality of five drinking wells at different distances from the runway of the Kyiv airport zone was analyzed.

У складних природних, техногенних і антропогенних умовах, коли одночасно на якість води безпосередньо в підземній частині гідросфери або через інші компоненти навколишнього середовища впливають різні фактори забруднення, оцінка якості підземних вод приймається на конкретного персонажа. Проведення постійного моніторингу стану підземних вод, порівняння та оцінка відповідності концентрацій забруднюючих речовин встановленим нормативам дає можливість оцінити фактичний стан підземних вод на території аеропорту та прилеглих територій за вмістом забруднюючих речовин. Основними джерелами забруднення підземних вод внаслідок експлуатації авіаційної техніки є дощові та талі води, аварійні скиди нафтохімікатів, господарства зберігання паливно-мастильних матеріалів. Мета роботи: провести екологічну оцінку якості підземних вод в районі Міжнародного аеропорту Київ (Жуляни) за основними гідроекологічними показниками. Проаналізовано якість води п’яти питних колодязів на різній відстані від злітно-посадкової смуги зони аеропорту Київ.
Keywords: еcological assessment; groundwater; airport zone; екологічна експертиза; грунтові води; зона аеропорту; кафедра екології та екоменеджменту